Effect of Fertilizer Dosage and Watering Frequency on the Growth of Mucuna breacteata - Heri Setyawan; Wandha Atmaka Aji; Olivia Elfatma; Indra Kurniawan; Subakho Aryo Saloko; Cut Ocha Mutia Wisuda (SEAS (Sustainable Environment Agricultural Science), 2024)
The Mucuna bracteata plant has various benefits in the world of oil palm plantations. Apart from being a ground cover plant, Mucuna bracteta is also a source of organic matter in oil palm plantations. The availability of less arable land makes the need to develop Mucuna bracteata cultivation as a benchmark in anticipation of the impact of the increasing availability of arable land in oil palm plantations. A study has been carried out to determine the effect of P fertilizer dose and watering frequency on the growth of Mucuna breacteata, which has been carried out in the Education and Research Garden (KP-2) Akademi Komunitas Perkebunan Yogyakarta which is located in Papringan, Depok, Sleman, Yogyakarta. This study uses a factorial design consisting of two factors arranged in a complete random design. The first factor is the application of various doses of P fertilizer consisting of 3 levels, namely a dose of 1.5 g/plant, a dose of 3.0 g/plant, and a dose of 4.5 g/plant. The second factor is the frequency of watering which consists of 2 levels, namely 1 time a day and 1 time 2 times a day. The data of the research results were analyzed with various fingerprints at the real level of 5%. If there is a real difference, it will be continued with a test Duncan Multiple Range Test (DMRT) real level 5%. The results of the study showed that the application of P fertilizer with doses of 1.5 g, 3.0 g, and 4.5 g as well as the frequency of watering 1 time a day and 1 time 2 times a day, showed that the interaction of the two treatments had a real effect on the parameters of plant height, number of leaves, fresh weight of crown, and dry weight of crown. Meanwhile, the parameters of root fresh weight, root dry weight, and total number of root nodules showed no real interaction. However, the interaction of the two treatments has an effect on each treatment alone or separately.